DEVELOPMENT OF SOCIAL-EMOTIONAL LEARNING ASSESSMENT INSTRUMENTS IN IMPROVING THE TEACHING PROFESSION OF STUDENTS OF THE INDONESIAN LANGUAGE TEACHER PROFESSION PROGRAM, MUHAMMADIYAH UNIVERSITY OF PALEMBANG - Houtman; Surismiati; Haryadi; Refson; Supriatini; Ayu Wulandari; Gunawan; Sri Parwanti; Mustofa; Danto; Nyimas Inda Kusumawati (PKM Linggau: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Community service activities in the form of Compiling Social Emotional Learning Assessment Instruments in Improving Teaching Professionalism of Indonesian Language Teacher Profession Program Students, Muhammadiyah University of Palembang aims to provide knowledge and skills in compiling social-emotional learning assessment instruments that meet the requirements to measure the achievement of ongoing learning, especially from the social-emotional aspects of students. The ability to compile this instrument is expected to improve the professionalism of prospective teachers who are currently undergoing Professional Teacher education. The target audience in this PPM activity is 18 Indonesian Language Teacher Profession Education (PPG) students, FKIP, Muhammadiyah University of Palembang. This activity uses lecture, demonstration, and practice methods accompanied by questions and answers. The lecture method explains the concept of Social Emotional Learning and the scope of CASEL components. The demonstration method is used to show a work process, namely the stages of compiling the instrument, while the practice method is used to practice making instruments that meet the requirements. Meanwhile, the question-and-answer method is to provide participants with the opportunity to consult in overcoming obstacles in compiling students' social-emotional learning instruments. The availability of adequate experts in designing social-emotional assessment instruments in the PPG Study Program, the enthusiasm of participants, the support of faculty leaders for the implementation of activities, and supporting funds from the faculty are the supporters of the implementation of this PPM activity. The obstacles faced are that the participants do not yet have initial knowledge about social-emotional learning and limited time for training. The benefits that participants can get from this PPM activity include being able to compile and develop social-emotional learning assessment instruments that will later be used in assessing students' social-emotional development.